Answer:
1. (x-i3√2)(x+i3√2)
x² + 18 = 0
x² = -18
x = ±√(-18)
x = ±i3√2
(x-i3√2)(x+i3√2)=0
2. (x + 6i)(x - 6i)
x² - (6i)² = x² - (6²)(i²) = x² - 36i² = x² + 36
x² - (6i)² = (x + 6i)(x - 6i)
x² + 36 = (x + 6i)(x - 6i)
(x + 6i)(x - 6i)
3. x^4 - 625 = (x^2+25)(x+5)(x-5)
a^2-b^2 = (a+b)(a-b)
x^4 - 625 = (x^2+25)(x^2-25)
x^2-25 = (x+5)(x-5)
x^4 - 625 = (x^2+25)(x+5)(x-5)
4. y^4 + 12y^2 + 36 =
(4^2 + 6)^2 =
((y + √-6) (y - √-6))^2=
(y + i √6)^2(y - i √6)^2 =
(y^2 + 2i √ 6y - 6)(y^2 - 2i √6y - 6)
5. Y³ + 2y² + 16y + 32
Y² (y+2) + 16 (y+2)
(Y² + 16) (y+2)